2015
DOI: 10.1155/2015/284595
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality and Respiratory Health among Adolescents from the United Arab Emirates

Abstract: Purpose. To examine the role of air quality in relation to chronic bronchitis, emphysema, asthma, wheeze, and dry cough among adolescents from the United Arab Emirates (UAE). Methods. A survey was administered on 6,363 adolescents from 9 UAE regions. Data consists of demographic, socioeconomic, residential, and behavioural variables, such as location of residence, residing near industry/gas stations/dumpsites/construction sites, residing near overhead power line/plants, exposure to tobacco, residential exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
(35 reference statements)
1
12
0
3
Order By: Relevance
“… 22 A cross-sectional survey conducted in nine regions of UAE also reported the impact of different risk factors on respiratory health. 21 This is consistent with other international studies, where chronic bronchitis was associated with passive smoking, cigarette smoking, air pollution, and exposure to dust or gas. 36 , 37 Regardless of the triumphs and endeavors in the tobacco control by the UAE, there remain many obstacles to achieve the goal.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 22 A cross-sectional survey conducted in nine regions of UAE also reported the impact of different risk factors on respiratory health. 21 This is consistent with other international studies, where chronic bronchitis was associated with passive smoking, cigarette smoking, air pollution, and exposure to dust or gas. 36 , 37 Regardless of the triumphs and endeavors in the tobacco control by the UAE, there remain many obstacles to achieve the goal.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of these studies demonstrated that tobacco smoking causes high blood pressure, 23 influence the epithelial dysplasia status, 22 and is a significant predictor of dry cough and wheeze. 21 …”
Section: Resultsmentioning
confidence: 99%
“…The study results reveal an alarming rise in the proportion of smokers among university students (28.2%) for both sexes compared to a previous study conducted in 2008 (12.5%) for both sexes (Mandil et al, 2007) and the results based on the data from the National Study of Population Health in the UAE (NSPHUAE) (2007-2009) which accounted for 13.9% among adolescents between the ages of 13 to 20 years (Barakat-Haddad, Zhang, Siddiqua, & Dghaim, 2015). A high prevalence of smoking among university students was encountered in other studies, 46.9% in Greece (Alexopoulos, Jelastopulu, Aronis, & Dougenis, 2010), 31.6% in Turkey (Öncel et al, 2011), 31% in Gaza, Palestine (Abu Shomar, Lubbad, El Ansari, Al-Khatib, & Alharazin, 2014), and as low as 25.3% in a university in Tehran (Jafari et al, 2011).…”
Section: Discussionmentioning
confidence: 49%
“…Within the same context of negative coefficients, the probability is expected to be less than 50% of the sample owing to the negative beta coefficients yielded from the model. Whereas, contrary to this observation a significant predictive factor for smoking in other studies was having both parents as smokers (Öncel et al, 2011;Barakat-Haddad et al, 2015;Aslam, Zaheer, Rao, & Shafique, 2014;Geidne, Beckman, Edvardsson, & Hulldin, 2016;Merdad, Al-Zahrani, & Farsi, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…Considering the size of RTA fleet of buses and the number of operation hours, the amount of pollution caused is significant and should be eliminated if the aforementioned UAE vision is to be achieved. Number of investigations have indicated that the UAE suffer from significant pollution [18]. For example, CO2 emissions per capita (metric tons) in the UAE is 19.9 compared to world average of 4.9 and 3.9 for Middle East and North Africa respectively [19].…”
Section: Despite the Fact The Rta Buses Are Running With Euro 4 Andmentioning
confidence: 99%